(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
World integration has led to the formation of a fundamentally new sociocultural space, in which interpersonal and interethnic communication occupies a special place. The new social order of society has changed the status of a foreign language as an academic discipline. The main goal of the training was to master the English language as a means of oral and written communication in various spheres of social and professional activity in the context of intercultural communication